Establishment of common data element for myasthenia gravis and its significance in the researches of phenotypes - Hai-feng LI; Yu HUANG; Xiang⁃jun CHEN (Chinese Journal of Contemporary Neurology and Neurosurgery, 2020)
Common data element (CDE) is standardized data elements that describe the characteristics of diseases, with the aim of promoting the structure and standardization of data, reducing the missing of important data and narrowing the differences between different researchers in the process of data acquisition. The diversity and heterogeneity of disease phenotypes require rational preparation of CDE to reflect the disease phenotypes from multiple dimensions. This paper introduces the special problems in the establishment of CDE of myasthenia gravis (MG) and discusses the related issues on the process of developing CDE, reviews the CDE of MG domestic and abroad, and discusses the significance of CDE in the researches of MG phenotypes. DOI：10.3969/j.issn.1672⁃6731.2020.01.007